Patterns of Susceptibility in an Outbreak of Bordetella pertussis: Evidence from a Community-Based Study - David M Moore; Richard G Mathias (Canadian Journal of Infectious Diseases)
OBJECTIVE: To describe an outbreak of Bordetella pertussis and to assess which factors were associated with the development of clinical pertussis in children and adults during the outbreak.